Pengaruh Aplikasi Poro Belajar Bahasa Jepang Kanji terhadapKemampuan Kanji pada Mahasiswa Prodi Pendidikan Bahasa Jepang FKIP Universitas Riau - Ramadhany; Merri Silvia Basri; Adisthi Martha Yohani (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2022)
Learning media is one of the supporting components that can help a learning process. One of the learning media that can be applied is the application media in learning kanji. The application is called "Poro Learn Japanese Kanji (Poro)". The purpose of this study was to see the effect of applying application media on kanji learning for class of 2019 students of Japanese Language Education, UniversitasRiau. This study used the experimental method. The data for this study were collected by distributing pre-test and post-test questions via Google Form. The results of this study indicate that of the 34 samples, 24 people experienced the effect of increasing value changes in learning kanji after the application of Poro application media. Then 3 people experienced a decrease in value, while the other 7 people did not have any effect.